2018
DOI: 10.1088/1741-2552/aac8ec
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinter applied picosecond pulsed electric fields for targeted manipulation of proliferation and lineage specific gene expression in neural stem cells

Abstract: Changes in cell metabolism, proliferation, and gene expression after picosecond pulsed electric field exposure are cell type specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…In addition, the effect of pulsed ES on stem cell proliferation is cell type specific. Petrella et al [ 38 ] compared the effects of picosecond pulsed electric field on NSCs and MSCs. Pulsed ES has no influence on MSC proliferation but improves NSC proliferation and astrocyte-specific differentiation by upregulating GFAP after 24 h under 40 kV/cm.…”
Section: Electrical Stimulation Enhances Stem Cell Neural Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the effect of pulsed ES on stem cell proliferation is cell type specific. Petrella et al [ 38 ] compared the effects of picosecond pulsed electric field on NSCs and MSCs. Pulsed ES has no influence on MSC proliferation but improves NSC proliferation and astrocyte-specific differentiation by upregulating GFAP after 24 h under 40 kV/cm.…”
Section: Electrical Stimulation Enhances Stem Cell Neural Differentiationmentioning
confidence: 99%
“…An amine functionalized MWCNT and polyethylene glycol dipropionate (PEGDA) polymer composite complex was fabricated into a tunable porous neural scaffold that could promote neural stem cell proliferation and neuronal differentiation via a stereolithography 3D printer [ 77 ]. Petrella et al used a 3D printer anchored with a picosecond pulse electric field electrode to print MSCs and NSCs [ 38 ]. Their data indicated that 40 kV/cm at 1800 pulses can promote astrocyte specific differentiation but not alter differentiation of MSCs.…”
Section: Effect Of Electrical Stimulation Through Conductive Materials On Neural Differentiationmentioning
confidence: 99%
“…However, limited by the technique of the picosecond pulse generator, psPEFs, especially their potential electro‐biological effects, have rarely been studied. Petrella et al [2018] noted the promising application of a 730 ps, 1016 V/m psPEF in neural stimulation and neural stem cell proliferation. In addition, our simulation work found that picosecond voltage pulse matching an impulse‐radiated antenna could achieve a focus in breast tissue, and when the input was 1 V Gaussian pulse (200 ps in pulse width), the intensity of the focal spots was 62.8 V/m [Li et al, 2018b], which further indicated the promising potential of psPEFs in noninvasive neuromodulation.…”
Section: Introductionmentioning
confidence: 99%
“…Anesthetics are currently drugs with the greatest direct impact on the nerves, and are applied most frequently. As a commonly-used anesthetic, sevoflurane used to be considered as a landmark drug in inhalation anesthesia (7), which is characterized by low dose of muscle relaxant and rapid postoperative recovery, and it is often used in anesthesia for children (8,9). However, there have been different reports on the effect of sevoflurane on nerves so far.…”
Section: Introductionmentioning
confidence: 99%